Avec qui traduit-on ? Les imaginaires de la traduction poétique - Christine Lombez (Itinéraires)
With whom does the poetry translator translate? To what extent is he accompanied by other voices, other imaginaries than his own, that will give his translation its full meaning? These questions are particularly important when we consider the interpretative choices of the translator, who might also be a poet himself. This paper probes the different poetic imaginaries and addresses the relations (empathic or antagonistic) that poetry translators develop with the source text.